Lower Lateral Femoral Index as a Significant Risk Factor for Non-Contact Anterior Cruciate Ligament Rupture: A Case-Control Study - Ahmad Syahril Anwar; Husnul Fuad Albar; Reza Mahruzza Putra (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Introduction: Anterior Cruciate Ligament (ACL) injury is one of the most common knee ligament injuries, particularly in the athletic population. Anatomical risk factors, such as knee bone morphology, are thought to play a crucial role in injury susceptibility. One parameter under investigation is the Lateral Femoral Index (LFCI), which describes the shape of the lateral femoral condyle. This study aimed to analyze the difference in LFCI in patients with ACL rupture compared to normal individuals as a potential risk factor. Methods: This study employed an observational analytic design with a case-control approach, conducted at H. Adam Malik General Hospital, Medan. The sample consisted of 50 subjects divided into two groups: 25 patients with an arthroscopically confirmed diagnosis of ACL rupture (case group) and 25 healthy individuals with no history of knee injury (control group). The LFCI was measured from true lateral projection knee radiographs. An independent T-test was used for statistical analysis to compare the mean LFCI difference between the two groups. Results: The mean age of the study subjects was 30.68 ± 5.35 years. The measurements revealed that the mean LFCI in the ACL rupture group was significantly lower (0.68 ± 0.56) compared to the control group (0.74 ± 0.56). This difference was statistically significant (p < 0.001). Conclusion: There is a significant difference in the Lateral Femoral Index (LFCI) between patients with ACL rupture and normal individuals. A lower LFCI value can be considered an anatomical risk factor for ACL rupture.